The Changes in Students’ Conception on the Concept of Reaction Order in the Implementation of Conceptual Change Model Supported By Worksheets - Permatasari, Rosalina Eka; Putriawati, Wiwin (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2026)
Misconceptions about reaction order can persist among preservice chemistry teachers, yet evidence remains limited on how individual conceptions change across successive stages of a conceptual-change intervention. This study explored within-person trajectories during a conceptual change model (CCM) implemented through a conceptual change module (CCMo) and a separate ontology–epistemology–axiology (OEA) worksheet. This exploratory embedded multiple-case study used a qualitative-dominant mixed-methods approach. Six preservice chemistry teachers were purposively selected based on misconception-classified responses to a 16-item four-tier diagnostic test. Qualitative evidence from verification, cognitive-conflict, equilibration, worksheet, and final-reconstruction activities was integrated with descriptive diagnostic-test counts and participant questionnaires. At the first verification, one participant was classified as having a misconception, one as not knowing the concept, and four as knowing the concept; at the second verification, five were classified as having a misconception and one as not knowing the concept. During standard CCMo-supported equilibration, five participants achieved full performance, whereas only one achieved full performance on the OEA worksheet. Final reconstruction was rated sufficient for two participants and poor for four. On the final diagnostic test, five participants showed fewer misconception-classified responses than at baseline, while one participant increased from three to five. These heterogeneous patterns indicate that correct task performance during equilibration did not consistently persist into later reconstruction or diagnostic assessment. The findings provide process-level evidence for individualized remediation and support future controlled studies, but they do not establish the causal effectiveness of the CCM or the added value of the worksheet.